2022
DOI: 10.3390/pathogens11020249
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic Dysfunction in Dogs Naturally Infected with Angiostrongylus vasorum—A Narrative Review

Abstract: This narrative review aims to describe Angiostrongylus vasorum-induced hemostatic dysfunction of dogs with emphasis on clinical and laboratory findings as well as potential therapeutic strategies for the bleeding patient. Canine angiostrongylosis (CA) is a disease with potentially high morbidity and mortality in endemic areas and with fatal outcome often associated with either severe respiratory compromise, pulmonary hypertension and right-sided heart failure, or hemostatic dysfunction with severe bleeding. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 98 publications
(201 reference statements)
0
10
0
Order By: Relevance
“…However, gingival and cutaneous bleeding diathesis and mucosal bleeding in different anatomical localisations were the most common findings. A fair number of dogs presented with neurological signs, which is in alignment with the current literature (Willesen et al ., 2022). These findings are of high clinical significance and stress the importance of canine A. vasorum infection being considered a major differential diagnosis in any dog with either unexplained coagulopathy or neurological signs A. vasorum endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…However, gingival and cutaneous bleeding diathesis and mucosal bleeding in different anatomical localisations were the most common findings. A fair number of dogs presented with neurological signs, which is in alignment with the current literature (Willesen et al ., 2022). These findings are of high clinical significance and stress the importance of canine A. vasorum infection being considered a major differential diagnosis in any dog with either unexplained coagulopathy or neurological signs A. vasorum endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, diagnoses were made based on serum antigen detection, and a prevalence similar to those in this study was reported [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ], demonstrating that although prevalence is generally low, this disease is widely distributed throughout much of the continent, showing its emerging nature. Despite this, to date, there have only been two previous studies in Spain that have evaluated the presence of this disease in different regions, so an epidemiological map was needed to help determine the current status of canine angiostrongylosis in Spain [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the most frequent clinical presentation is cardiorespiratory by nature, caused by the presence of adults and by the migration of larvae [ 8 , 9 ]. Fatal infection is often associated with severe respiratory compromise, pulmonary hypertension, right heart failure, and/or hemostatic dysfunction with fatal bleeding [ 10 ]. However, some infected animals may not show clinical signs during infection, or these infection may be non-specific, making diagnosis difficult [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Serum biochemistry (Idexx VetTest Chemistry Analyser) demonstrated hypoalbuminaemia (albumin 16 g/L, Ref. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]) and hypocholesterolaemia (cholesterol 1.63 mmol/L, Ref.…”
Section: Case Presentationmentioning
confidence: 99%
“…The patient had no travel history outside the UK and was fully vaccinated, thus relatively excluding non-endemic infectious causes (direct or immune-mediated) of thrombocytopenia and anaemia (dirofilariasis, ehrlichiosis, babesiosis, anaplasmosis and so on). Angiostrongylosis is a differential for thrombocytopenia, as part of the bleeding diathesis caused by this parasite 26 and perhaps as a trigger for associative IMTP. 27,28 Angiostrongylosis was not supported in this patient based on negative blood antigen testing.…”
Section: Differential Diagnosismentioning
confidence: 99%